"I Didn't Become a Professor to Teach High School": Examining College Educators' Perceptions of Culture in Early College High Schools. Issue 1 (2nd April 2020) - Mollet, Amanda L.; Stier, Matthew J.; Linley, Jodi L.; Locke, Leslie A.
ABSTRACT: Early College High Schools (ECHSs) represent a unique approach for educating minoritized students. As a hybrid, joining a traditional high school with a college or university, the central mission of ECHSs is to provide academic support and resources for students' high school completion and substantial college credit. The success of the ECHS model appears in students' rates of completion, college participation, and college degree attainment. With the unique merged context of K-12 and higher education, this exploratory study examined the perceptions of ECHS culture for participating higher education faculty and staff. Drawing on interviews from seven participants, we identified norms, values, beliefs, and assumptions that influence the ways our participants' work within the ECHS setting. We include implications for research and practice.